Mobile Learning for Transforming English Writing Skills: A Systematic Review (2013–2023) - Khamraeva Shavkatovna, Dilfuza; Hashim, Harwati; Jamaludin, Khairul Azhar (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Language learning has been transformed by the use of mobile learning (m-learning) technologies in educational settings, especially with growing interest in improving productive skills. Considering m-learning as a prominent menace, the objective of this paper was to investigate the effects of m-learning tools on English as a foreign language (EFL) learners’ English writing proficiency. This study offers a thorough review of modern m-learning tactics and technologies. Three research questions were developed to frame this investigation. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) technique was used to assess and categorize 21 selected papers published between 2013 and 2023 from the Scopus and Web of Science (WOS) databases. The subject of the study and methodologies were assessed by the content analysis of published articles. Convenience, enhanced engagement, motivation, self-paced learning, learning autonomy, and interactivity were the other six main study findings that were found. Consequently, this review can serve as a starting point for future research projects aimed at managing m-learning as well as new avenues of investigation for the development of English writing abilities. Finally, some recommendations for further research are included in the conclusion section.